Detection and survival of Candida albicans in soils. Issue 6 (19th July 2021) - Sautour, Marc; Lemaître, Jean‐Paul; Ranjard, Lionel; Truntzer, Caroline; Basmaciyan, Louise; Depret, Géraldine; Hartmann, Alain; Dalle, Frédéric
Abstract: Candida albicans is the most common human fungal pathogen. This yeast is described as a commensal of human and animal mucosa, and very few studies have focused on its isolation in natural environments. We investigated the presence of C. albicans in a large panel of French soils. Because a culture‐based method didn't allow isolation of the yeast in a panel of 70 soils, we adapted a nested‐PCR for detecting C. albicans DNA in a panel of 460 soils. Only 7 of the 460 soil samples (1.5%) were PCR‐positive for Candida albicans . To understand which parameters influence the survival of the yeast, we studied the decline of a population of C. albicans over a period of one month in a collection of 20 soils collected throughout France. C. albicans was able to survive up to 30 days in 80% of the soils tested. Using a Spearman correlation test, we showed that the short‐term survival of C. albicans in soils was correlated with some soils chemical factors such as pH and presence of some minerals (Al, Mn, and Na). Concerning survival after 30 days, Cation Exchange Capacity (CEC) and clay content were identified as beneficial determinants of the long‐term survival of C. albicans in soils. Abstract : In this study, we developed a nested‐PCR approach to detect DNA of Candida albicans in soils, and we confirmed for the first time the presence of DNA signatures of the yeast in 1.5% of 460 French soil samples tested. We also investigated the survival of the yeast in a panel of 20 soils, and our results point out the role of soils' chemical properties in determining the survival of C . albicans .